Genetic diversity and haplotypes of Cysticercus tenuicollis isolates from slaughtered sheep and goats in Elazig and Bingol provinces of Turkey - Karakoc, Sirvan; Kesik, Harun Kaya; Celik, Figen; Selcuk, Muhammed Ahmed; Kilinc, Seyma Gunyakti; Simsek, Sami (Wiley, 2024)
Background: The cestode Taenia hydatigena uses canids, primarily dogs, as definitive hosts, whereas the metacestode larval stage cysticercus infects a range of intermediate hosts, including domestic animals such as goats, sheep and pigs. Objectives: In this study, we aimed to determine the genetic differences and haplotypes of Cysticercus tenuicollis isolates obtained from sheep and goats slaughtered in the Bingol and Elazig provinces of Turkey. Methods: C. tenuicollis isolates were collected from 44 sheep and 26 goats slaughtered in slaughterhouses in Bingol and Elazig. After the isolation of total genomic DNA from C. tenuicollis isolates, the genetic characterization of the partial mitochondrial cytochrome oxidase 1 (CO1) gene region (866 bp) was amplified using specific primers by polymerase chain reaction (PCR), the products were then sequenced, and haplotype and genetic diversity analyses were carried out. Results: As a result of the haplotype network analyses, 34 different haplotypes were detected around the main haplotype (Hap02) arranged in a star-like configuration and separated from other haplotypes by 1-28 mutation steps and covering 22.85% (16/70) of all isolates. Twenty-seven polymorphic fields were detected, 77.77% (21/27) of which were parsimony-informative, and secondary haplotype and nucleotide diversity were observed. Additionally, we detected high intraspecies haplotype diversity (hd: 0.933) and high nucleotide diversity (pi: 0.00383), with 27 different nucleotide variation positions among the haplotypes of the isolates. Tajima's D value was negative, indicating population expansion and/or selection purification. The significantly negative Fu's Fs values indicated recent population expansion or the presence of expected rare haplotypes. Conclusion: The results of this study confirmed that C. tenuicollis isolates clustered in one lineage and were closely related to the relevant reference sequences in different countries, confirming the circulation of C. tenuicollis in different geographical regions.
Keywords: Cysticercus tenuicollis; sheep; goat; mt-CO1; PCR; haplotype